Applicable law in matrimonial property regime disputes - Pogorelčnik Vogrinc, Neža (Array, 2020)
The paper presents the regulation of the applicable law as determined in Council Regulation (EU) 2016/1103 of 24 June 2016 implementing enhanced cooperation in the area of jurisdiction, applicable law and the recognition and enforcement of decisions in matters of matrimonial property regimes. It concludes that the new EU arrangement has made it easier for spouses to determine the applicable law and evaluates the suitability of the connecting factors provided by Regulation 2016/1103. The paper also challenges the examination of these connecting factors as of the time of the conclusion of the marriage and assumes that their exclusion under exceptional circumstances is difficult to achieve. It compares the connecting factors with those provided by Slovenian and Croatian private international law in theory, and provides practical examples of the differences resulting from the new European arrangement. The paper further examines the hypothesis that the possibility of agreement on the choice of law will cause many problems in practice, and provides possible solutions. Throughout the paper, the system established by Regulation 2016/1103 is compared with other European regulations and the relevant case law of the CJEU, but the author primarily focuses on the changes in Slovenian and Croatian case law caused by the application of Regulation 2016/1103.